2023
DOI: 10.1039/d3bm01046e
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of assay-ready hepatocyte monolayers by chemically-induced ice nucleation: preservation of hepatic function and hepatotoxicity screening capabilities

Ruben M. F. Tomás,
Robert Dallman,
Thomas R. Congdon
et al.

Abstract: Controlled ice nucleation enables cryopreservation of primary hepatocytes monolayers, in assay ready format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…23 This approach has been used for cryopreserving A549, HepG2, and primary hepatocytes in 96-well plates with nearquantitative cells recovered and maintenance of total cell functionality. 24 In this work, we demonstrate a robust method for cryopreserving Vero cells in monolayer format in both 12and 24-well plates using polyampholytes combined with chemically-induced ice nucleation. These cells exhibit healthy morphology and cell viability, and grow post-thaw equal to freshly cultured cells.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 This approach has been used for cryopreserving A549, HepG2, and primary hepatocytes in 96-well plates with nearquantitative cells recovered and maintenance of total cell functionality. 24 In this work, we demonstrate a robust method for cryopreserving Vero cells in monolayer format in both 12and 24-well plates using polyampholytes combined with chemically-induced ice nucleation. These cells exhibit healthy morphology and cell viability, and grow post-thaw equal to freshly cultured cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…24-well plates were positioned on a Corning XT CoolSink 96F and placed in a −80 °C freezer overnight. Cells were thawed by removing from the −80 °C, adding https://doi.org/10.1021/acs.biomac.4c00760Biomacromolecules XXXX, XXX, XXX−XXX…”
mentioning
confidence: 99%
“…18 Cryopreserving cells in smaller microwells, such as 96-well plates, are especially challenging due to a delay in ice nucleation of smaller volumes (supercooling), whereby ice formation can occur at −15 °C. 18,19 Extracellular ice formation is required to increase osmotic gradients and promote cellular dehydration, so supercooling can lead to lethal intracellular ice formation. 20 There is also high well-to-well variability due to the stochastic nature of ice nucleation, leading to a range of freezing values.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Macromolecular cryoprotectants, based on ice-binding proteins or synthetic polymers (especially polyampholytes), have been shown to dramatically improve monolayer storage of cells, especially in larger microwell formats (e.g., 12- and 24-well plates). Gibson et al have reported near 100% recovery of various cell lines including primary cell monolayers . Cryopreserving cells in smaller microwells, such as 96-well plates, are especially challenging due to a delay in ice nucleation of smaller volumes (supercooling), whereby ice formation can occur at −15 °C. , Extracellular ice formation is required to increase osmotic gradients and promote cellular dehydration, so supercooling can lead to lethal intracellular ice formation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation